Enhanced output voltage of nano energy harvester with diverse textiles. (3rd July 2019) - Lim, Kyungmin; Kim, Do-Kyung; Jeong, Jae Bum; Choi, Suyoung; Biswas, Swarup; Tibaldi, Alexandra; Ma, Tae-Young; Lee, Suwoong; Kim, Jong-Hyoung; Ko, Jaehoon; Cho, Hanchul; Lee, Sohee; et al.
Abstract: We demonstrate the electrical properties of nano energy harvesters (NEHs) with various textiles for smart textiles that can be applied to the next generation wearable electronics. Output voltages and currents of NEHs with various fabrics, such as a cotton, rayon and wool that have different triboelectricity were measured. Cotton, rayon and wool shows the maximum output voltages of 1.250, 3.313 and 4.063 V, respectively. In addition, output currents of those textiles were 0.75, 4.4, 1.063 μA, respectively. Wool, in particular, which has the highest triboelectricity of 350 V exhibits the highest output voltage.